Yakov Polonsky in Ryazan Region. Review of Chekurin, L. V. (Ed.) (2014). Jakov Petrovich Polonskij: lichnost’ i tvorchestvo v istorii russkoj kul’tury [Yakov Polonsky: Personality and Creative Work in the History of Russian Culture]. Rуazan: PervopeshatnikЪ - Reshetova, A. A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2016)
The paper is an analytical review of the collective study Yakov Polonsky: Personality and Creative Work in the History of Russian Culture, published in Ryazan in 2014. The monograph is a joint effort of a group of scholars from Ryazan and their colleagues from Moscow and Veliky Novgorod in connection with the discussion of topical issues of Y. P. Polonsky’s creative work studies. The research aims to demonstrate the importance of the work under review in the context of regional literary criticism development: the appearance of the monograph is a landmark in the research history of the 19th century writer’s poetic heritage that is considered in many aspects in the system of Russian classics. The methodological basis of the work is imposed by its purpose, i.e. the need to analyze the first collective monograph on the legacy of an original Russian 19th century poet in relation to earlier works of local and national literary studies, which makes it possible to use the historical and cultural, historical and functional, and comparative-typological methods. The author concludes that the reviewed work is of considerable scholarly value; within its framework the authors offer a modern look at the key aspects of Y. P. Polonsky’s poetics, the original character of his poetry, making an attempt to uncover the symbolic implications of his poetic imagery, and clarify the genre peculiarities of the poet’s works.